2009
DOI: 10.1128/jb.01834-08
|View full text |Cite
|
Sign up to set email alerts
|

Role of Class A Penicillin-Binding Proteins in the Expression of β-Lactam Resistance in Enterococcus faecium

Abstract: Peptidoglycan is polymerized by monofunctional D,D-transpeptidases belonging to class B penicillin-binding proteins (PBPs) and monofunctional glycosyltransferases and by bifunctional enzymes that combine both activities (class A PBPs). Three genes encoding putative class A PBPs (pbpF, pbpZ, and ponA) were deleted from the chromosome of Enterococcus faecium D344R in all possible combinations in order to identify the glycosyltransferases that cooperate with low-affinity class B Pbp5 for synthesis of peptidoglyca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
56
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(59 citation statements)
references
References 19 publications
3
56
0
Order By: Relevance
“…Previous work has shown that daptomycin resistance in Enterococcus faecium and Enterococcus faecalis may be accompanied by decreases in membrane fluidity (6,15). Interestingly, our previous characterization of these 2 strains showed no changes in this property between the strains under standard growth conditions (6).…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…Previous work has shown that daptomycin resistance in Enterococcus faecium and Enterococcus faecalis may be accompanied by decreases in membrane fluidity (6,15). Interestingly, our previous characterization of these 2 strains showed no changes in this property between the strains under standard growth conditions (6).…”
Section: Resultsmentioning
confidence: 95%
“…These phenotypes are part of other studies in our lab on the effects of beta-lactams on bacterial autolysins. We are currently investigating the differential effect of class A penicillin binding protein (PBP) inactivation on susceptibility to daptomycin and antimicrobial peptides and whether ceftaroline and/or ampicillin exert their effects on VRE through these targets (15). Additional evidence by others suggests that low-molecular-weight PBPs, such as ddcP, which influences D-alanine-D-alanine carboxypeptidase activity (16), warrant study as well, particularly with the possible tangential effects on vancomycin MIC by ceftaroline.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Penicillin resistance in E. faecium is mediated via point mutations in the housekeeping pbp5 gene leading to reduced penicillin binding to the expressed protein (Jureen et al, 2004;Rice et al, 2004;Rice et al, 2009). Mutated pbp5' was also found as an integral part of conjugative transposons, like Tn5382, thus encoding transferable ampicillin and VanB-type vancomycin resistance (Carias et al, www.intechopen.com 1998; Valdezate et al, 2009).…”
Section: Penicillin Resistancementioning
confidence: 99%
“…Surprisingly, in some cases, such as the Gram-positive organisms Bacillus subtilis (21), Enterococcus faecalis (1), and Enterococcus faecium (28), it has been shown that strains lacking all class A PBPs are viable and have only slight differences in peptidoglycan composition. In contrast, in Streptococcus pneumoniae, the deletion of class A PBP1a and PBP2a was lethal (13), and in S. aureus, the only class A PBP, PBP2, is essential for viability in methicillin-susceptible strains and in methicillin-resistant strains exposed to ␤-lactam antibiotics (24).…”
mentioning
confidence: 99%